Comparison of ambient solvent extraction methods for the analysis of fatty acids in non-starch lipids of ﬂour and starch - Bahrami, Niloufar; Yonekura, Lina; Linforth, Rob S.T.; Carvalho da Silva, Margarida; Hill, Sandra; Penson, Simon; Chope, Gemma; Fisk, Ian D. (Wiley, 2014)
BACKGROUND: Lipids are minor components of ﬂours, but are major determinants of baking properties and end-product quality. To the best of our knowledge, there is no single solvent system currently known that efﬁciently extracts all non-starch lipids from all ﬂours without the risk of chemical, mechanical or thermal damage. This paper compares nine ambient solvent systems (monophasic and biphasic) with varying polarities: Bligh and Dyer (BD); modiﬁed Bligh and Dyer using HCl (BDHCL); modiﬁed BD using NaCl (BDNaCl); methanol–chloroform–hexane (3:2:1, v/v); Hara and Radin (hexane–isopropanol, 3:2, v/v); water-saturated n-butanol; chloroform; methanol and hexane for their ability to extract total non-starch lipids (separated by lipid classes) from wheat ﬂour (Triticum aestivum L.). Seven ambient extraction protocols were further compared for their ability to extract total non-starch lipids from three alternative samples: barley ﬂour (Hordeum vulgare L.), maize starch (Zea mays L.) and tapioca starch (Manihot esculenta Crantz).